5-(Adamantan-1-yl)-3-[(2-methoxyethyl)sulfanyl]-4-phenyl-4H-1,2,4-triazole - Ali A. El-Emam; Ebtehal S. Al-Abdullah; Hanadi H. Asiri; Suchada Chantrapromma; Hoong-Kun Fun (Acta Crystallographica Section E, 2012)
In the title adamantyl derivative, C21H27N3OS, the terminal methoxyethyl unit is disordered over two orientations with a refined site-occupancy ratio of 0.846 (6):0.154 (6). The 1,2,4-triazole ring is statistically planar [r.m.s. deviation = 0.002 (2) Å] and the phenyl substituent is almost perpendicular to its mean plane [dihedral angle = 83.57 (11)°]. No directional intermolecular interactions were observed in the crystal structure.